THE INFLUENCE OF SOCIAL MEDIA ON McD PUSCHASING DECISIONS DURING THE ISRAELI AND PALESTINIAN CONFLICTS - Arda, Mutia; Andriany, Dewi (Proceeding International Seminar of Islamic Studies, 2024)
After providing assistance in the form of 4,000 free food packages to Israeli soldiers, McDonald's or McD fast food restaurants were widely boycotted in various countries, including Indonesia. This happened because this company from the United States (US) was considered inhumane. McD is considered to support Israel's actions. In several of its latest uploads, the McDonald's Indonesia Instagram account itself has been widely commented on by netizens with calls of disappointment, boycott and support for Palestine. Several accounts also commented using #boycotmcdonalds. This research aims to determine the influence of social media, especially Instagram, on McD purchasing decisions. The sample for this research was 100 students at the Muhammadiyah University of North Sumatra. The data analysis technique used is simple regression analysis. The results of this research show that social media had a positive and significant influence on McD purchasing decisions during the Israeli and Palestinian conflict. Based on the R2 value, it is known that 25,3% of social media influences McD purchasing decisions